Perancangan Sistem Laporan Pengeluaran Dana Bantuan Operasional Sekolah (Bos) Pada Upt Satuan Pendidikan SMP Negeri 6 Tangerang - Achmad Rachmat; Sari Indriana; Amelia Rosa (UNIVERSITAS RAHARJA, 2021)
School Operational Assistance (BOS) is a government program that is basically to provide funding for non-personnel operating costs for junior high schools (SMP) as implementing compulsory education programs. In supporting the management of School Operational Assistance (BOS) funds at schools, an information system has been created that can assist in managing BOS funds. The School Operational Assistance Management (BOS) Management Information System was created because inaccurate and incomplete data were often found at the UPT Education Unit of SMP Negeri 6 Tangerang. Causing financial statements every month to be not timely. Therefore this financial statement system was made to support the data to be accurate and complete and the financial statements also become timely. To illustrate the model design and system design using the Unified Modeling Language (UML). The results of this study are a financial reporting system that is designed using the PHP programming language, MySQL database, and laptops are code editors. For testing the system using the Blackbox method, in order to test the functionality of the system.